Assessment of Combined Trichoderma-Enriched Biofertilizer and Nutrients Solutions on the Growth and Yield of Strawberry Plants - Khan, Fawad; Kim, Na Eun; Bhujel, Anil; Jaihuni, Mustafa; Lee, Deog Hyun; Basak, Jayanta Kumar; Kim, Hyeon Tae (Journal of Biosystems Engineering, 46(3), 2021)
Purpose The use of biofertilizers not only decreases the level of a nutrient solution but also improves the growth of plants and reduces the risk of environmental pollution. In this study, the impact of Trichoderma- enriched biofertilizer (poultry manure composted and Trichoderma harzianum YC459 (TEB), standard nutrient solution (SNS), and the combination of both (TEB + SNS) were utilized to evaluate the growth, yield, and nutritional quality of strawberry plants ( Fragaria × ananassa Duch.). Method The strawberry plants were planted in four treatments — control soil (CS, without TEB and SNS), T1 (SNS), T2 (TEB), and T3 (50% SNS + 50% TEB) — in a controlled greenhouse. Several scientific instruments such as a ubiquitous broadcast network (UBN) farm link control management system, sensor nodes, nutrient controller, composting reactor, digital refractor meter, dry oven, digital balance, and different chemical techniques were used for a particular purpose. Results Consequently, analysis of variance was performed, and a significant increase in yield values (123.07–145.83% and 88.46–100.00%) was recorded over control by T3 and T1, respectively. Also, the vegetative growth parameters, total soluble solids, ascorbic acid, and total sugar content were observed higher in T3. Conclusion It was observed that the combined use of Trichoderma- enriched biofertilizer with the standard nutrient solution could improve the growth, yield, and quality of the strawberry plant.